Leucism in South American Lungfishes Lepidosiren paradoxa Fitzinger, 1837 (Osteichthyes, Dipnoi, Lepidosirenidae) from Argentina - Romano, Luis A.; Pedrosa, Virgínia F. (Brazilian Journal of Veterinary Pathology, 2020)
The present study reports a case of leucism in South American Lungfish Lepidosiren paradoxa captured in Corrientes, Argentina. It was observed a change in cutaneous pigmentation, and it was concluded that it was leucism and not albinism, since there was a decrease of tegumentary melanin pigment and normal pigmentation in the retina.